The making of incarnation : a novel - McCarthy, Tom, 1969 May 22- (Alfred A. Knopf, 2021)
"From the author of Remainder and Satin Island (which was short-listed for the Booker Prize), a high-tech odyssey through CGI studios, wind tunnels, and drone research centers, where the limits of healing, entertaining, revelation, and destruction are continually being transformed. A kaleidoscopic exploration of motion and how the forces that compel and impel us continues to defy capture and understanding. The historical starting point: Lillian Gilbreth, first investigator and architect of time and motion studies, spurred in part by the conundrum of how to raise twelve children (remember Cheaper by the Dozen, the memoir written by her children). The fictional or mythic starting point (one of many): Anthony Garnett's insomnia, and the inevitable sheep-counting he experienced after visiting a sheep farm, the images of sheep he'd observed, prompting in his mind a schematic tracking their movements, unpredictable yet governed by a general drive or aim, the location of one animal at a given moment, the corresponding location of another at the same moment, each linked by lines of transit, switchbacks and detours, lines themselves dictated by the larger flow of the collective mass, as well as operative strings of need, fear, rivalry, yearning, linking individuals randomly to one another. The originating seed of the company he founds, Pantaray, PLC., whose name was inspired by a fragment of pre-Socratic Heraclitus, who famously also noted that you cannot step into the same river twice, the first axiom of motion studies. The Making of Incarnation explores the myriad facets of the intersection of technology and the human, an intersection that continues to re-create the possibility of what we are able to imagine."--